Influence of agitation methods of irrigants after methylene blue-mediated PDT on the bonding interface of a fiber post cementation system - Galvani, Lucas David [UNESP]; Costa, Joatan Lucas de Sousa Gomes [UNESP]; Besegato, João Felipe [UNESP]; Zaniboni, Joissi Ferrari [UNESP]; Escalante-Otárola, Wilfredo Gustavo [UNESP]; Kuga, Milton Carlos [UNESP] (Elsevier, 2022)
Background: This study evaluated the effects of final agitation methods of irrigants to remove methylene blue and sodium hypochlorite residues after PDT-assisted endodontic treatment on the bond strength of fiber posts cemented with etch-and-rinse adhesive and conventional resin cement. Methods: Ninety bovine teeth were endodontically treated. In sequence, post space preparation followed by methylene blue-mediated PDT and sodium hypochlorite (NaOCl) irrigation were performed. Six final irrigations protocols for dye and NaOCl removal were performed prior to cementation with etch-and-rinse adhesive (Adper Scocthbond Multipurpose) and conventional dual resin cement (RelyX ARC): Conventional endodontic irrigation (CEI), passive ultrasonic irrigation (PUI), mechanical agitation with XP Endo Finisher (XPF), XP Clean (XPC) or Easy Clean (ECL) and distilled water (NCO - control). After fiber post cementation, push-out bond strength test was performed at different thirds of the post space. Failure mode was also analyzed. ANOVA and Tukey's post-hoc test was used for data analysis (α=5%). Results: PUI, XPF e XPC protocols showed the highest bond strength values with no difference among them (p > 0.05), although they were similar to NCO, regardless of the post space third. CEI e ECL showed similar bond strength values, regardless of the third (p > 0.05). Adhesive failure was the most incident for CEI and ECL, while mixed and cohesive failures were predominant in PUI, XPF, XPC and NCO groups. Conclusions: Mechanical agitation of distilled water with XPF, XPC and PUI after methylene blue-mediated PDT and irrigation with 2.5% sodium hypochlorite promoted bond strength of the resin cementation system in post space dentin comparable to control group.
Keywords: Adhesion; Bond strength; Fiber posts; Mechanical agitation; Methylene blue; Photodynamic therapy; Root canals